Effect of dexmedetomidine on hemodynamic responses during the propofol induction period, skull-pin application and skin incision in patients under going craniotomy - Saringcarinkul, Ananchanok; Punjasawadwong, Yodying; Kongtonkul, Natta; Werawong, Kornkamol (Biomedical Sciences and Clinical Medicine, 2015)
Objectives The authors of this study hypothesized that dexmedetomidine (DEX) would attenuate hemodynamic changes during the propofol induction period, skull-pin application and skin incision in supratentorial craniotomy, when compared with fentanyl. Methods Thirty patients (18-70 years), who were scheduled for elective intracranial surgery, received infusions of DEX at 1 μg/kg (group D) or fentanyl at 2 μg/kg (group F) before propofolbased anesthesia. Propofol was started at 3.0 μg/mL on a target control syringe pump and titrated to maintain a similar level of sedation by using the Bispectral index in both groups. The hemodynamic variables were recorded continuously and analyzed for the results. Results Overall, the arterial pressures [systolic (Ps), diastolic (Pd) and mean arterial pressure (MAP)] increased after receiving infusion of DEX at 1 μg/kg and were higher than those in patients receiving fentanyl for the whole period of the study. Ps, Pd, and MAP in group F decreased after 2 μg/kg of fentanyl infusion and decreased further through propofol induction, and then increased by responding to endotracheal intubation. Pd and MAP increased in both groups after skull pin fi xation, but with no signifi cant difference from the pre-skull pin fi xation value in each group. Ps, Pd and MAP in both groups did not change much after skin incision, when compared to pre-skin incision values. The induction and total doses of propofol in group D were smaller than those in group F, and group D required less fentanyl intraoperatively when compared to group F, but with no statistical signifi cance. Conclusion DEX at 1 μg/kg was no more effective than fentanyl at 2 μg/kg on blunting hemodynamic responses to endotracheal intubation, skull-pin fixation, and skin incision in craniotomy patients, even though it helped to stabilize the hemodynamic during propofol induction.